Analysis of Human Resource Competencies and Workload on Employee Performance through Organizational Commitment within the Employee Scope of the Village Community Empowerment Office in Langkat Regency - Kristina; Muhammad Alfahmi; Nizamuddin (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze HR Competency and Workload on Employee Performance through Organizational Commitment to the Employee Scope of the Village Community Empowerment Office in Langkat Regency. The data analysis technique used is associative research with the help of the SPSS program. This study uses path analysis. The sample in this study was 82 respondents. Primary data collection uses questionnaires. The results of the study show that (1) the human resource competency variable has a direct insignificant influence on organizational commitment, and a significant direct influence on employee performance, as well as a significant indirect influence on employee performance through organizational commitment in the Village Community Empowerment Office in Langkat Regency. (2) The workload variable has a significant direct influence on organizational commitment, and an insignificant direct influence on employee performance, as well as a direct and significant influence on employee performance through organizational commitment to the Village Community Empowerment Office in Langkat Regency. (3) The variable of organizational commitment has a significant direct influence on the performance of employees at the Village Community Empowerment Office in Langkat Regency.